PERBEDAAN MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK PENGURUS HIMPUNAN MAHASISWA JURUSAN PADA FAKULTAS TEKNIK DAN DESAIN DAN FAKULTAS ILMU SOSIAL DAN HUMANIORA DI UNIVERSITAS BUNDA MULIA - Maria Dwi Yanika Hesti Nugraha; Yana Ningsih (Universitas Bunda Mulia, 2011)
At the university level, many students who take an active role in the stewardship of the organization. Students Association (HMJ) is an intra-campus students who are majoring in science within the scope of a particular faculty. HMJ organizations focus more on non-academic activities that are scientific, reasoning, and professional development programs in accordance with scientific studies. The study was conducted to determine differences in intrinsic motivation and extrinsic motivation on board Department Student Association.This research is a quantitative study using a measuring instrument with a Likert scale questionnaire. The subject of this study were students who were active in the management department at the University Student Association of the Mother. Analytical techniques used in this study is an Independent Samples T-Test. Based on test results Independent Samples T-Test as seen from the results of Levene's test showed a p-value = 0.568 indicates that there were no differences in intrinsic motivation and extrinsic motivation on board Department Student Association.However, intrinsic motivation and extrinsic motivation, intrinsic motivation where the differences seen on board HMJ Faculty of Engineering and Design tends to be lower than the caretaker HMJ Faculty of Social Sciences and Humanities. As for extrinsic motivation, the board of HMJ School of Social Sciences and Humanities tend to be higher than the board HMJ Faculty of Engineering and Design.Keyword: Intrinsic Motivation, Extrinsic Motivation, Student.